Epigenetic-Transcriptional Regulation of Fatty Acid Metabolism and Its Alterations in Leukaemia - Maher, Michael; Diesch, Jeannine; Casquero, Raquel; Buschbeck, Marcus (Frontiers in Genetics, 2018)
In recent years fatty acid metabolism has gained greater attention in haematologic cancers such as acute myeloid leukaemia. The oxidation of fatty acids provides fuel in the form of ATP and NADH, while fatty acid synthesis provides building blocks for cellular structures. Here, we will discuss how leukaemic cells differ from healthy cells in their increased reliance on fatty acid metabolism. In order to understand how these changes are achieved, we describe the main pathways regulating fatty acid metabolism on the transcriptional level and highlight the limited knowledge about related epigenetic mechanisms. We explore these mechanisms in the context of leukaemia and consider the relevance of the bone marrow microenvironment in disease management. Finally we discuss efforts to interfere with fatty acid metabolism as a therapeutic strategy along with the use of metabolic parameters as biomarkers.